Phylogenetic position and morphological polymorphism of the chafer, Clinterocera nigra (Coleoptera: Scarabaeidae: Cetoniinae) from Taiwan. Issue 8 (3rd August 2022) - Wu, Li-Wei; Chen, Ming-Yu; Li, Chun-Lin
Abstract: Three mitochondrial genomes of the cetoniine beetle, Clinterocera nigra (Kano, 1931 ) were assembled via next-generation sequencing. The newly sequenced mitogenomes all have 37 genes, showing standard gene order and annotation as the other insects. To examine their phylogenetic positions and relationships between their elytral color (red-spot and melanistic forms) and sequence variation, a total of 118 public mitogenomes of Scarabaeidae were used to infer a maximum-likelihood (ML) tree. Our results show that the melanistic form is grouped within red-spot ones, revealing a population level variation on the elytra color. Our work also provides the first mitogenomic reference of myrmecophilous chafers.